2019
DOI: 10.3389/fonc.2019.01079
|View full text |Cite
|
Sign up to set email alerts
|

Chronic BDE-47 Exposure Aggravates Malignant Phenotypes and Chemoresistance by Activating ERK Through ERα and GPR30 in Endometrial Carcinoma

Abstract: Environmental exposure to certain compounds contribute to cell plasticity, tumor progression and even chemoresistance. 2,2′,4,4′-tetrabromo diphenyl ether (BDE-47), one of the most frequently detected polybrominated diphenyl ethers (PBDEs) in environmental and biological samples, is a known estrogen disruptor closely associated with the development of hormone-dependent cancers. However, the effect of BDE-47 on endometrial carcinoma (EC), an estrogen-dependent cancer, remains to be elucidated. Mechanisms of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The so-called “legacy BFRs” are defined as obsolete, but they are still widely monitored due to their ubiquity in the environment. Zhang et al [ 27 ] evaluated the role in EC. They employed an in vitro and in vivo analysis of the effects of 2,2′, 4,4′-tetrabromo diphenyl ether (BDE-47), one of the most frequent polybrominated diphenyl ethers (PBDEs) found in environmental and biological samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called “legacy BFRs” are defined as obsolete, but they are still widely monitored due to their ubiquity in the environment. Zhang et al [ 27 ] evaluated the role in EC. They employed an in vitro and in vivo analysis of the effects of 2,2′, 4,4′-tetrabromo diphenyl ether (BDE-47), one of the most frequent polybrominated diphenyl ethers (PBDEs) found in environmental and biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…With their estrogenic potential, it has been shown in mouse studies that NP and OP interfere with estrogenic activity with effects on the uterus resulting in endometrial proliferation [ 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been recently shown that GPER1 knockdown or antagonism enhances the sensitivity of gastric cancer cells to Cp, suggesting that GPER1 can be a target to improve Cp chemotherapeutic efficacy against gastric tumors developing chemoresistance [ 69 ]. Similarly, it has been shown that exposure to the estrogen disruptor, 2,2′,4,4′-tetrabromo diphenyl ether-47 (BDE-47), attenuates the sensitivity of endometrial carcinoma cells to Cp, thus eliciting chemoresistance, at least in part via a GPER1 signaling pathway [ 70 ]. Overall, the contribution of sex hormonal receptors in the development of Cp chemoresistance is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…ERα contributes to EC through the interaction with several proteins [such as DAX-1, R receptor-binding cancer antigen expressed on SiSo cells (RCAS1), etc.] and the crosstalk with some signaling pathways [such as epidermal growth factor receptor (EGFR)/ERK signaling pathway and insulin/insulin receptor signaling pathway] (Table 3) [27,[39][40][41]. For example, ERα and ERβ5 are co-expressed in the nuclei of endometrial adenocarcinoma cells, and they can form heterodimers that enhance the hormone sensitivity of Ishikawa cells, thereby promoting EC [42].…”
Section: Co-regulatormentioning
confidence: 99%
“…First, upstream regulators regulate the transcriptional activity of ERα and promotes the development of EC, especially in proliferation [26]. Second, ERα can promote the occurrence of EC together with co-regulators [27,28]. Third, ERα mediates EC proliferation, metastasis and apoptosis through downstream proteins or genes [29].…”
Section: Roles Of Erα In Endometrial Carcinomamentioning
confidence: 99%